Saudi Arabian Developments - Altbach, Philip (International Higher Education, 2011)
Saudi Arabia spends significantly on higher education, and its higher education system has expanded impressively in recent years. Now the Kingdom is seeing to upgrade its higher education system and to create a more systematic approach to academic development. Challenges remain, but the effort is proceeding.